Degrees of chitosan deacetylation from white shrimp shell waste as dental biomaterials - Sularsih Sularsih; Anita Yuliati; Coen Pramono D (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Chitosan is biomaterial improved for various dentistry applications because it is biocompatible, degradable, nontoxic, and not carcinogenic. The main parameter affecting the characteristics of chitosan is deacetylation degree. Purpose: This study is aimed to determine the degree of deacetylated of chitosan derived from white shrimp shell waste used as dental biomaterial. Methods: White shrimp shells were crushed into powder. Next, deproteination process was conducted with 3.5% NaOH solution, demineralized with 1N HCl solution, and then depigmented with 90% acetone solution into chitin powder. Deacetylation process was then conducted by soaking the chitin powder in 50% NaOH solution for 6 h at 65° C to produce white powder of chitosan. Afterwards, deacetylation degree test was conducted by using Fourier Transform Infrared Spectrophotometer (FTIR) to calculate the ratio of the absorption bands between the absorbance peak of amide group about 1655 cm–1 and the absorbance peak of hydroxyl group about 3450 cm–1. Results: The result of the deacetylation degree test on the chitosan powder derived from white shrimp shell waste was high, about 85.165%, and had the eligible form, solubility, and pH. Conclusion: It can be concluded that the deacetylation degree of chitosan from white shrimp shells could reach 85.165%.Latar belakang: Kitosan merupakan biomaterial yang dikembangkan untuk berbagai aplikasi kedokteran gigi karena biokompatibel, dapat didegradasi, tidak toksik dan tidak karsinogenik. Parameter utama yang mempengaruhi karakteristik kitosan adalah derajat deasetilasi. Tujuan: Tujuan dari penelitian ini adalah mengetahui derajat deasetilasi kitosan dari limbah kulit udang putih sebagai biomaterial kedokteran gigi. Metode: Kulit udang putih dihaluskan menjadi serbuk. Setelah itu dilakukan proses deproteinasi dengan larutan NaOH 3,5%, demineralisasi dengan larutan HCl 1N, depigmentasi dengan larutan aseton 90% sehingga menjadi serbuk kitin. Proses deasetilasi dilakukan dengan merendam serbuk kitin dalam larutan NaOH 50% selama 6 jam pada suhu 65° C sehingga dihasilkan serbuk putih kitosan. Uji derajat deasetilisasi menggunakan metode spektrofotometer Fourier Transform Inframerah (FTIR) dengan menghitung nilai perbandingan pita serapan antara puncak absorbansi gugus amida sekitar 1655 cm–1, dan puncak absorbansi gugus hidroksil sekitar 3450 cm–1. Hasil: Hasil uji derajat deasetilasi serbuk kitosan dari limbah kulit udang putih adalah tinggi yaitu sebesar 85.165% dan memiliki bentuk, kelarutan dan pH yang memenuhi syarat. Kesimpulan: Dapat disimpulkan derajat deasitilasi kitosan dari kulit udang putih adalah 85,165%.